2015
DOI: 10.1016/j.cell.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Uptake and Runx2 Synergize to Orchestrate Osteoblast Differentiation and Bone Formation

Abstract: In the originally published author list, we inadvertently misspelled Takashi Iezaki's surname. The author list has been corrected online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(165 citation statements)
references
References 0 publications
5
157
2
1
Order By: Relevance
“…Specifically, the expression of early stage osteogenesis marker COL1, osteoblast-secreted late stage marker OCN critical for matrix mineralization [40], GLUT1 responsible for glucose uptake (its expression found to positively correlates with osteogenesis [41]), and adipogenesis marker PPARγ responsible for fatty acid storage and glucose metabolism was quantified. Diabetic PDCs showed significantly higher (by approximately 17-fold, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the expression of early stage osteogenesis marker COL1, osteoblast-secreted late stage marker OCN critical for matrix mineralization [40], GLUT1 responsible for glucose uptake (its expression found to positively correlates with osteogenesis [41]), and adipogenesis marker PPARγ responsible for fatty acid storage and glucose metabolism was quantified. Diabetic PDCs showed significantly higher (by approximately 17-fold, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…qPCR confirmed that diabetic PDCs responded to the rhBMP-2/7 rescue in high glucose osteogenic media by upregulations of early stage (COL1) and late stage (OCN) osteogenic markers and the glucose transporter GLUT1 known to positively correlate to osteoblastic differentiation [41], as well as the downregulation of adipogenic marker PPARγ. By contrast, diabetic BMSCs only exhibited a small increase in COL1 expression but no significant changes in OCN or GLUT1 expression after 2 weeks of rhBMP-2/7 treatment in high glucose osteogenic media.…”
Section: Discussionmentioning
confidence: 96%
“…For AMPK phosphorylation assay, GST-Smurf1 and GST-Runx2 constructs were generated and purified as previously described (Ferron et al, 2013; Wei, 2015). AMPK phosphorylation assay of GST-Smurf1 WT and S148A was performed using previously described method (Wei, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…In addressing this question, we recently found that, just as it is the case for neurons, glucose is the main nutrient of osteoblasts and it is transported in osteoblasts in an insulin-independent manner through a facilitative glucose transporter, Glut1 . Mice lacking Glut1 specifically in osteoblasts displayed a severe delay in skeletogenesis prenatally and developed osteopenia and glucose intolerance postnatally because of a compromised osteoblast differentiation, a decrease in bone formation and reduced circulating levels of insulin [59]. Further molecular and genetic investigations revealed that to achieve its multiple functions, glucose inhibits two distinct functions of AMPK.…”
Section: Mutual Dependence Between Bone and Glucose Homeostasismentioning
confidence: 99%
“…Since Runx2 is the main transcriptional regulator of Osteocalcin expression, by promoting Runx2 accumulation, glucose uptake in osteoblasts favors Osteocalcin expression [60, 61] and thereby whole-body glucose homeostasis. The relationship between Runx2 and glucose uptake goes a step further since Runx2 in turn regulates Glut1 expression in osteoblasts [59]. By uncovering an amplification chamber in which Glut1, Runx2 and osteocalcin signaling pathway in coordinating osteoblast differentiation, bone formation and whole-body glucose homeostasis, these findings certainly provide one rationale for why bone would regulate glucose homeostasis (Figure 3).…”
Section: Mutual Dependence Between Bone and Glucose Homeostasismentioning
confidence: 99%